A positive electrode sheet of a lithium ion battery and a lithium ion battery

By designing a multi-layer structure in the lithium-ion battery positive electrode sheet and using LiMPO4 and LixNiaCobMncA1-a-b-cO2 as active materials, the shortcomings in the existing lithium-ion battery positive electrode materials are solved, and high energy density and high safety performance are achieved.

CN116417562BActive Publication Date: 2025-03-11BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111663578.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-03-11
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have shortcomings in terms of energy density and safety. Lithium iron phosphate materials have low energy density, while ternary materials have strong oxidation and poor safety.

Method used

A lithium-ion battery cathode sheet including a positive electrode current collector, a first active material layer, a second active material layer and a third active material layer are used. LiMPO4 is used in the first and second active material layers and LixNiaCobMncA1-a-b-cO2 is used in the third active material layer. Through the design of this hierarchy, the energy density and safety performance of the battery are improved.

Benefits of technology

It achieves a higher energy density and better safety performance, taking into account the high safety of lithium iron phosphate materials and the high energy density of ternary materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003535878670000121
    Figure GDA0003535878670000121
  • Figure GDA0003535878670000131
    Figure GDA0003535878670000131
Patent Text Reader

Abstract

The present application provides a positive electrode sheet of a lithium ion battery and a lithium ion battery. The positive electrode sheet of the lithium ion battery includes a positive electrode collector, a first active material layer located on the surface of the positive electrode collector, a second active material layer close to a side of a separator of the lithium ion battery, and a third active material layer located between the first active material layer and the second active material layer. The active materials in the first active material layer and the second active material layer are the same or different. The active materials in the first active material layer and the second active material layer respectively include LiMPO4, wherein M is selected from one or more of Mn, Fe, Co, Ni, and Ti; the active material in the third active material layer includes LixNiaCobMncA1‑a‑b‑cO2, wherein 0.9≤x≤1.1, 0.3≤a≤0.95, 0≤b≤0.5, 0≤c≤0.5, and A is selected from one or more of Zr, Ti, Y, Al, Ba, and Sr.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet of a lithium-ion battery and a lithium-ion battery. Background Art

[0002] Currently, the positive electrode materials of lithium-ion batteries on the market are mostly lithium iron phosphate materials or ternary materials. Lithium iron phosphate materials, such as lithium iron phosphate and lithium iron manganese phosphate, have good stability and the prepared batteries have high safety. They are now widely used in the field of new energy vehicles. However, the gram capacity and discharge voltage platform of lithium iron phosphate materials are relatively low, and they do not have an advantage in energy density. Although ternary materials have the advantage of high energy density, they are highly oxidizable, unstable, and have poor safety. How to strike a balance between high energy density and high safety has always been an important research direction in the industry. Summary of the invention

[0003] In view of this, the present application provides a positive electrode sheet for a lithium-ion battery, which is applied to the lithium-ion battery. Compared with the existing lithium iron phosphate battery and ternary material battery, it has higher energy density and better safety performance.

[0004] In a first aspect, the present application provides a positive electrode sheet for a lithium-ion battery, comprising a positive electrode current collector, a first active material layer located on the surface of the positive electrode current collector, a second active material layer close to one side of a separator of the lithium-ion battery, and a third active material layer located between the first active material layer and the second active material layer. The active material in the first active material layer and the active material in the second active material layer are the same or different. The active material in the first active material layer and the active material in the second active material layer include LiMPO4, wherein M is selected from one or more of Mn, Fe, Co, Ni, and Ti; the active material in the third active material layer includes LixNiaCobMncA1-ab-cO2, wherein 0.9≤x≤1.1, 0.3≤a≤0.95, 0≤b≤0.5, 0≤c≤0.5, and A is selected from one or more of Zr, Ti, Y, Al, Ba, and Sr. First active material layer Second active material layer

[0005] The positive electrode sheet of the lithium-ion battery provided by the present application, because the active material in the active material layer on the side close to the current collector includes LiMPO4, compared with the direct application of ternary materials to prepare the positive electrode sheet, the thermal diffusion rate of the electrode sheet and the risk of needle puncture short circuit are reduced, which greatly improves the safety performance of the battery. The active material layer on the side close to the separator of the lithium-ion battery also includes active LiMPO4, which further slows down the side reaction between the electrolyte and the entire positive electrode sheet and improves the durability of the battery; at the same time, the positive electrode sheet of the lithium-ion battery of the present application is also provided with a ternary material layer in the middle, and the active material of the ternary material layer includes LixNiaCobMncA1-ab-cO2, which overcomes the defect of low capacity of directly using active LiMPO4 as the positive electrode active material, and improves the overall energy density of the electrode sheet. The positive electrode sheet provided by the present application is applied to lithium-ion batteries, taking into account the advantages of lithium iron phosphate materials and ternary materials at the same time, and the prepared battery phase has a high energy density and good safety performance.

[0006] According to one embodiment of the present application, the positive electrode sheet includes a positive electrode collector, a first active material layer located on the surface of the positive electrode collector, a third active material layer located on the surface of the first active material layer on the side facing away from the positive electrode collector, and a second active material layer located on the surface of the third active material layer on the side facing away from the first active material layer.

[0007] According to one embodiment of the present application, the thickness of the first active material layer is L1, the thickness of the second active material layer is L2, and the thickness of the third active material layer is L3, L1+L2+L3=L; the relationship between the thickness L1 of the first active material layer, the thickness L2 of the second active material layer and the thickness L3 of the third active material layer satisfies: 1μm≤L1≤0.9*L, 1μm≤L2≤0.9*L, 0.1*L≤L3≤0.8*L.

[0008] According to one embodiment of the present application, the relationship between the thickness L1 of the first active material layer, the thickness L2 of the second active material layer and the thickness L3 of the third active material layer satisfies: 0.3*L≤L1≤0.8*L, 0.2L≤L2≤0.6*L, 0.1*L≤L3≤0.6*L.

[0009] According to one embodiment of the present application, in the first active material layer, the median particle size of the active material LiMPO4 is D501, in the second active material layer, the median particle size of the active material LiMPO4 is D502, and in the third active material layer, the median particle size of the active material LixNiaCobMncA 1-a-b-c The median particle size of O2 is D503, where (L1 / D501) / (L3 / D503)≤8, 0.05≤(L2 / D502) / (L3 / D503)≤8.

[0010] According to one embodiment of the present application, the median particle size D501 of the active material LiMPO4 in the first active material layer, the median particle size D502 of the active material LiMPO4 in the second active material layer, and the median particle size D503 of the active material LixNiaCobMncA in the third active material layer 1-a-b-c The relationship between the median particle size D503 of O2 satisfies: 0.1≤(L1 / D501) / (L3 / D503)≤6, 0.2≤(L2 / D502) / (L3 / D503)≤6.

[0011] According to one embodiment of the present application, in the third active material layer, the active material LixNiaCobMncA 1-a-b-c The molar content of Ni element in O2 is ε, the thickness of the first active material layer L1, the thickness of the second active material layer L2 and the active material LixNiaCobMncA in the third active material layer 1-a-b-c The relationship between the molar content ε of the Ni element in O2 satisfies: 0.1≤L1 / (ε*L3)≤5. According to one embodiment of the present application, the median particle sizes D501 and D502 of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 0.3μm≤D501≤1.5μm, 0.3μm≤D502≤1.5μm; the particle size distribution of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfies: 1≤(D901-D101) / D501≤4, 1≤(D902-D102) / D502≤4.

[0012] According to one embodiment of the present application, the median particle sizes D501 and D502 of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 0.6μm≤D501≤1.2μm, 0.6μm≤D502≤1.2μm; the particle size distribution of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfies: 2≤(D901-D101) / D501≤3, 2≤(D902-D102) / D502≤3.

[0013] According to one embodiment of the present application, the median particle size D503 of the active material LixNiaCobMncA1-ab-cO2 in the third active material layer satisfies: 1μm≤D503≤15μm; the particle size distribution of the active material LixNiaCobMncA1-ab-cO2 in the third active material layer satisfies: 2≤(D903-D103) / D503≤3.

[0014] According to one embodiment of the present application, the median particle size D503 of the active material LixNiaCobMncA1-ab-cO2 in the third active material layer satisfies: 3 μm≤D503≤6 μm.

[0015] According to one embodiment of the present application, the positive electrode conductive agents in the first active material layer, the second active material layer and the third active material layer are each independently selected from one or more of carbon nanotubes, conductive carbon black, and graphene; the positive electrode binders in the first active material layer, the second active material layer and the third active material layer are each independently selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile and polyacrylate.

[0016] According to one embodiment of the present application, the active material LiMPO4 includes LiFePO4, and the active material LixNiaCobMcO2 includes LiNi0.8Co0.1Mn0.1O2.

[0017] The second aspect of the present application provides a method for preparing a positive electrode sheet of a lithium ion battery, the method comprising: providing a positive electrode collector, preparing a first active material layer on at least one side surface of the positive electrode collector, preparing at least one third active material layer on the side surface of the first active material layer away from the positive electrode collector, preparing a second active material layer on the side surface of at least one third active material layer away from the first active material layer, the second active material layer is located on the side close to the separator of the lithium ion battery, the active material in the first active material layer and the active material in the second active material layer are the same or different, the active material in the first active material layer and the active material in the second active material layer include LiMPO4, wherein M is selected from one or more of Mn, Fe, Co, Ni, and Ti; the active material in the third active material layer includes LixNiaCobMncA1-ab-cO2, wherein 0.9≤x≤1.1, 0.3≤a≤0.95, 0≤b≤0.5, 0≤c≤0.5, and A is selected from one or more of Zr, Ti, Y, Al, Ba, and Sr.

[0018] According to one of the embodiments of the present application, the method for preparing a first active material layer on the surface of the positive electrode current collector comprises: coating a first positive electrode slurry on at least one side surface of the positive electrode current collector and drying it, the first positive electrode slurry comprising active material LiMPO4, a first positive electrode conductor and a first positive electrode binder; the method for preparing a third active material layer on the surface of the first active material layer comprises: coating a third positive electrode slurry on a side surface of the first active material layer away from the current collector and drying it, the third positive electrode slurry comprising active material LixNiaCobMncA1-ab-cO2, a third positive electrode conductor and a third positive electrode binder; the method for preparing a second active material layer on the surface of the third active material layer comprises: coating a second positive electrode slurry on the surface of the third active material layer and drying it, the second positive electrode slurry comprising active material LiMPO4, a second positive electrode conductor and a second positive electrode binder.

[0019] According to one embodiment of the present application, the method for preparing the positive electrode sheet of the lithium-ion battery includes: coating a first positive electrode slurry on the surface of a positive electrode current collector to form a first coating layer, wherein the first positive electrode slurry includes an active material LiMPO4, a first positive electrode conductor and a first positive electrode binder; the method for preparing a third active material layer on the surface of the first active material layer includes: coating a third positive electrode slurry on a side of the first coating layer away from the current collector to form a second coating layer, wherein the third positive electrode slurry includes an active material LixNiaCobMncA1-ab-cO2, a third positive electrode conductor and a third positive electrode binder; coating a second positive electrode slurry on a side of the second coating layer away from the first coating layer to form a third coating layer and drying the second positive electrode slurry.

[0020] The third aspect of the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet of the lithium-ion battery described in the present application or the positive electrode sheet of the lithium-ion battery prepared by the method for preparing the positive electrode sheet of a lithium-ion battery described in the present application.

[0021] A fourth aspect of the present application provides an electric vehicle comprising the lithium-ion battery described in the present application. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0023] The present application provides a positive electrode sheet of a lithium ion battery, comprising a positive electrode collector, a first active material layer located on the surface of the positive electrode collector, a second active material layer close to a side of a separator of the lithium ion battery, and a third active material layer located between the first active material layer and the second active material layer, wherein the active materials in the first active material layer and the second active material layer are the same or different, and the active materials in the first active material layer and the active materials in the second active material layer respectively comprise LiMPO4, wherein M is selected from one or more of Mn, Fe, Co, Ni, and Ti; the active material in the third active material layer comprises LixNiaCobMncA1-ab-cO2, wherein 0.9≤x≤1.1, 0.3≤a≤0.95, 0≤b≤0.5, 0≤c≤0.5, and A is selected from one or more of Zr, Ti, Y, Al, Ba, and Sr.

[0024] In the positive electrode sheet of the lithium-ion battery provided in the present application, the ternary material and the LiMPO4 active material are not simply mixed, but an active material layer containing the active material LiMPO4 is respectively arranged on the side close to the current collector and the side close to the separator of the lithium-ion battery, and a ternary material active material layer is arranged in the middle; since the side close to the current collector is the active material layer containing the active material LiMPO4, compared with the prior art that directly uses the ternary material as the active material layer, it has a better coating effect on the positive current collector. When the battery is impacted by the outside world or undergoes a needle puncture test, the negative electrode material will preferentially contact and short-circuit with the positive electrode material on the positive electrode sheet, and can prevent the negative electrode material from directly short-circuiting with the positive current collector. Due to the short-circuit between the negative electrode material and the positive electrode material, compared with the short-circuit contact between the negative electrode material and the positive current collector, it has a larger resistance and a smaller short-circuit current, and is relatively safer. The lithium-ion battery positive electrode sheet of the present application also includes active material LiMPO4 in the active material layer on the side close to the diaphragm of the lithium-ion battery, and at least one ternary active material layer is arranged between the two active material layers, which can not only effectively reduce the side reaction between the ternary material and the electrolyte, but also, during the charge and discharge process, due to the high voltage platform of the active material LixNiaCobMncA1-ab-cO2 of the middle ternary active material, the prepared lithium-ion battery positive electrode sheet has strong stability and high energy density; the lithium-ion battery positive electrode sheet described in the present application is applied to lithium-ion batteries, taking into account the high safety of lithium iron phosphate material batteries in the prior art and the high energy density of ternary material batteries. In this embodiment of the present application, as long as the active material layer on the current collector side of the positive electrode sheet includes active material LiMPO4 and the active material layer on the diaphragm side of the lithium-ion battery also includes active material LiMPO4 and a ternary material layer is included between the two layers of active materials. That is to say, in this embodiment of the present application, as long as the active layer located on the outermost side is the active material LiMPO4, and the middle layer contains the ternary material layer, the middle layer can contain one or more layers of the ternary material layer, or it can simultaneously contain one or more layers of the ternary material layer and one or more layers of the active layer containing the active material LiMPO4. When the middle layer simultaneously contains the ternary material layer and the active layer containing the active material LiMPO4, the ternary material layer and the active layer containing the active material LiMPO4 can be arranged arbitrarily, as long as the middle layer contains the ternary material layer.

[0025] According to a specific embodiment of the present application, the active material LiMPO4 includes lithium iron phosphate, and the active material LixNiaCobMncA1-ab-cO2 includes LiNi0.8Co0.1Mn0.1O2.

[0026] According to a specific embodiment of the present application, the active materials in the first active material layer and the second active material layer both include lithium iron phosphate.

[0027] In the lithium-ion battery positive electrode sheet of the present application, the ternary material and lithium iron phosphate are not simply mixed, but lithium iron phosphate material layers are respectively arranged on the side close to the current collector and the side close to the separator of the lithium-ion battery, and the ternary material layer is arranged in the middle of the lithium iron phosphate material layer; since the side close to the current collector is the lithium iron phosphate layer, the lithium iron phosphate material has a better coating effect on the positive current collector than the ternary material, and when the battery is impacted by the outside world or undergoes a needle puncture test, the negative electrode material will preferentially contact and short-circuit with the positive electrode material on the positive electrode sheet, and can prevent the negative electrode material from directly short-circuiting with the positive current collector. Due to the short-circuit caused by the contact between the negative electrode material and the positive electrode material, compared with the short-circuit contact between the negative electrode material and the positive current collector, it has a larger resistance and a smaller short-circuit current, and is relatively safer. The positive electrode sheet of the lithium-ion battery of the present application is also a lithium iron phosphate layer on the side close to the separator of the lithium-ion battery, and at least one layer of ternary active material layer is arranged in the middle of the lithium iron phosphate layer, which can not only effectively reduce the side reaction between the positive electrode and the electrolyte, but also, during the charge and discharge process, due to the high voltage platform of the ternary active material in the middle, the prepared positive electrode sheet of the lithium-ion battery has strong stability and high energy density; the positive electrode sheet of the lithium-ion battery described in the present application is applied to the lithium-ion battery, taking into account the high safety of the lithium iron phosphate material battery in the prior art and the high energy density of the ternary material battery. In this embodiment of the present application, as long as the side of the positive electrode sheet close to the current collector and the side of the separator of the lithium-ion battery are lithium iron phosphate layers and the ternary material layer is included in the middle of the lithium iron phosphate layer. That is to say, in this embodiment of the present application, as long as the outermost layer is a lithium iron phosphate material layer and the middle layer contains a ternary material layer, the middle layer can contain one or more layers of ternary material layers, or it can simultaneously contain one or more layers of ternary material layers and one or more layers of lithium iron phosphate material layers. When the middle layer contains both a ternary material layer and a lithium iron phosphate material layer, the ternary material layer and the lithium iron phosphate material layer can be arranged arbitrarily as long as the middle layer contains a ternary material layer.

[0028] According to one embodiment of the present application, the positive electrode sheet includes a positive electrode current collector, a first active material layer located on the surface of the positive electrode current collector, a third active material layer located on the surface of the first active material layer on the side facing away from the positive electrode current collector, and a second active material layer located on the surface of the third active material layer on the side facing away from the first active material layer. In this embodiment, the positive electrode material layer includes a lithium iron phosphate layer located on the outermost side close to the current collector and a lithium iron phosphate layer close to the separator side of the lithium-ion battery, and a third active material layer located between the two layers of lithium iron phosphate.

[0029] According to one embodiment of the present application, the positive electrode conductive agents in the first active material layer and the second active material layer may be the same or different, and the positive electrode conductive agents in the first active material layer and the second active material layer are independently selected from one or more of acetylene black, carbon black, carbon nanotubes, carbon nanofibers, activated carbon and graphene, and conductive carbon black; the positive electrode binders in the first active material layer and the second active material layer may be the same or different, and are independently selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile and polyacrylate.

[0030] According to one embodiment of the present application, the positive electrode conductors in the first active material layer and the second active material layer are independently selected from one or more of carbon nanotubes, graphene and conductive carbon black; the positive electrode binder in the first active material layer and the second active material layer includes polyvinylidene fluoride.

[0031] According to one embodiment of the present application, the thickness of the first active material layer is L1, the thickness of the second active material layer is L2, and the thickness of the third active material layer is L3, L1+L2+L3=L; the relationship between the thickness L1 of the first active material layer, the thickness L2 of the second active material layer, and the thickness L3 of the third active material layer satisfies: 1μm≤L1≤0.9*L, 1μm≤L2≤0.9*L, 0.1*L≤L3≤0.8*L. The inventor of the present application found in the experimental process that when the relationship between the thickness L1 of the first active material layer, the thickness L2 of the second active material layer, and the thickness L3 of the third active material layer satisfies the above conditions, the prepared battery has the highest energy density and safety performance.

[0032] According to one embodiment of the present application, the thickness relationship between the first active material layer, the second active material layer and the third active material layer satisfies: 0.3*L≤L1≤0.8*L, 0.2*L≤L2≤0.6*L, 0.1L≤L3≤0.6*L. When the thickness relationship between the first active material layer, the second active material layer and the third active material layer further satisfies the above conditions, not only can the occurrence of side reactions be effectively weakened, but the lithium iron phosphate layer can also play a better blocking role on the overall thermal diffusion of the pole piece, ensuring the safety performance of the pole piece and avoiding thermal runaway. At the same time, the ternary material of the middle layer can maximize the advantages of high energy density.

[0033] According to one embodiment of the present application, in the first active material layer, the median particle size of the active material LiMPO4 is D501, in the second active material layer, the median particle size of the active material LiMPO4 is D502, and in the third active material layer, the median particle size of the active material LixNiaCobMncA 1-a-b-cThe median particle size of O2 is D503, where (L1 / D501) / (L3 / D503)≤8, 0.05≤(L2 / D502) / (L3 / D503)≤8.

[0034] According to an embodiment of the present application, the median particle size D501 of the active material LiMPO4 in the first active material layer, the median particle size D502 of the active material LiMPO4 in the second active material layer, and the median particle size D503 of the active material LixNiaCobMncA in the third active material layer are 1-a-b-c The relationship between the median particle size D503 of O2 satisfies: 0.1≤(L1 / D501) / (L3 / D503)≤6, 0.2≤(L2 / D502) / (L3 / D503)≤6.

[0035] The inventors of the present application have found that by controlling the thickness of each active material layer and the median particle size of the active material in each layer within the above range, the prepared lithium-ion battery positive electrode sheet can be applied to a lithium-ion battery, and the battery has good and stable charge and discharge performance. The inventors have further found that the ratio of the thickness of each active material layer and the median particle size of the active material side in each active material layer will affect the diffusion of lithium ions, thereby further affecting the charge and discharge performance of the lithium-ion battery.

[0036] According to one embodiment of the present application, the molar content of Ni in the active material LixNiaCobMcO2 in the third active material layer is ε, and the relationship between the thickness L1 of the first active material layer, the thickness L2 of the second active material layer and the molar content of Ni in the active material LixNiaCobMcO2 in the third active material layer is ε, which satisfies: 0.1≤L1 / (ε*L3)≤5. The molar content of Ni in the third active material layer LixNiaCobMcO2 is ε and the thickness of each layer of lithium iron phosphate layer is controlled within the above range, which further ensures the thermal stability of the pole piece and further improves the safety performance of the pole piece. The inventor of the present application found that the higher the nickel content of the active material in the ternary material layer located in the middle, the higher the ratio between the thickness of the lithium iron phosphate layer located close to the current collector and the thickness of the ternary material layer needs to be increased accordingly in order to ensure the energy density while ensuring the safety performance. In this way, the energy density of the pole piece can be ensured while having better safety performance.

[0037] According to one embodiment of the present application, the median particle sizes D501 and D502 of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 0.3μm≤D501≤1.5μm, 0.3μm≤D502≤1.5μm; the particle size distribution of the active material LiMPO4 in the first active material and the second active material layer respectively satisfies: 1≤(D901-D101) / D501≤4, 1≤(D902-D102) / D502≤4. According to one embodiment of the present application, the median particle sizes D501 and D502 of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 0.6μm≤D501≤1.2μm, 0.6μm≤D502≤1.2μm; the particle size distribution of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfies: 2≤(D901-D101) / D501≤3, 2≤(D902-D102) / D502≤3.

[0038] According to a specific embodiment of the present application, the median particle size D503 of the active material LixNiaCobMncA1-ab-cO2 in the third active material layer satisfies: 1μm≤D503≤15μm; the particle size distribution of the active material LixNiaCobMncA1-ab-cO2 in the third active material layer satisfies: 2≤(D903-D103) / D503≤3.

[0039] According to one embodiment of the present application, the median particle size D503 of the active material LixNiaCobMncA1-ab-cO2 in the third active material layer satisfies: 3 μm≤D503≤6 μm.

[0040] The median particle size and particle size distribution of LiMPO4 in the lithium iron phosphate layer, and the median particle size and particle size distribution of LixNiaCobMcO2 in the third active material layer are controlled within the above ranges. The positive electrode active material has good kinetic properties and cycle stability, and can optimize the stacking structure of particles inside the electrode, so that the prepared positive electrode has high compaction, good pore structure, and low tortuosity, which is conducive to lithium ion diffusion, further ensuring the overall charge and discharge performance of the lithium ion battery.

[0041] The present application also proposes a method for preparing a positive electrode sheet of a lithium-ion battery, comprising:

[0042] A positive electrode current collector is provided, a first active material layer is prepared on the surface of at least one side of the positive electrode current collector, at least one third active material layer is prepared on the surface of the first active material layer, and a second active material layer is prepared on the surface of at least one third active material layer, wherein the second active material layer is located on a side of a separator close to a lithium ion battery; the active material in the first active material layer and the active material in the second active material layer are the same or different, and the active material in the first active material layer and the active material in the second active material layer include LiMPO4, wherein M is selected from one or more of Mn, Fe, Co, Ni, and Ti; the active material in the third active material layer includes LixNiaCobMncA1-ab-cO2, wherein 0.9≤x≤1.1, 0.3≤a≤0.95, 0≤b≤0.5, 0≤c≤0.5, and A is selected from one or more of Zr, Ti, Y, Al, Ba, and Sr.

[0043] According to one embodiment of the present application, a method for preparing a first active material layer on the surface of a positive electrode collector comprises: coating a first positive electrode slurry on at least one side surface of the positive electrode collector and drying it, wherein the first positive electrode slurry comprises an active material LiMPO4, a first positive electrode conductor, a first positive electrode binder and a first solvent; a method for preparing a third active material layer on the surface of the first active material layer comprises: coating a third positive electrode slurry on a side surface of the first active material layer away from the current collector and drying it, wherein the third positive electrode slurry comprises an active material LixNiaCobMncA1-ab-cO2, a third positive electrode conductor, a third positive electrode binder and a third solvent; a method for preparing a second active material layer on the surface of the third active material layer comprises: coating a second positive electrode slurry on the surface of the third active material layer and drying it, wherein the second positive electrode slurry comprises an active material LiMPO4, a second positive electrode conductor, a second positive electrode binder and a second solvent.

[0044] According to an embodiment of the present application, the active material LiMPO4 includes lithium iron phosphate, and the active material LixNiaCobMncA1-ab-cO2 includes LiNi0.8Co0.1Mn0.1O2; the first positive electrode conductor is the same as or different from the second positive electrode conductor, and the first positive electrode conductor and the second positive electrode conductor are respectively selected from one or more of carbon nanotubes, graphene and conductive carbon black; the third positive electrode conductor is selected from one or more of carbon nanotubes, graphene and conductive carbon black; according to an embodiment of the present application, the first positive electrode binder is the same as or different from the second positive electrode binder, and is respectively selected from polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide , polyacrylonitrile and polyacrylate; the third positive electrode binder is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile and polyacrylate; the first solvent and the second solvent in the present application are solvents conventionally used in the preparation process of the positive electrode of lithium iron phosphate batteries in the art, such as N-methylpyrrolidone, and the third solvent is a solvent conventionally used in the preparation process of the positive electrode of a ternary material battery, such as N-methylpyrrolidone, which is not described in detail in the present application; in the present application, the ratio of the components in the first positive electrode slurry and the second positive electrode slurry is well known in the art, and the ratio of the components in the third positive electrode slurry is also well known in the art and is not described in detail.

[0045] According to one embodiment of the present application, the manufacturing process of the electrode sheet can also be to coat the first positive electrode slurry, the third positive electrode slurry and the second positive electrode slurry on at least one side of the positive electrode collector in sequence through a multi-layer coating device and then dry the whole. Specifically, the method includes: coating the first positive electrode slurry on the surface of the positive electrode collector to form a first coating layer, and the first positive electrode slurry includes active material LiMPO4, a first positive electrode conductor and a first positive electrode binder; the method for preparing the third active material layer on the surface of the first active material layer includes: coating the third positive electrode slurry on the side of the first coating layer away from the current collector to form a second coating layer, and the third positive electrode slurry includes active material LixNiaCobMncA1-ab-cO2, a third positive electrode conductor and a third positive electrode binder; coating the second positive electrode slurry on the side of the second coating layer away from the first coating layer to form a third coating layer and drying it, and the second positive electrode slurry includes active material LiMPO4, a second positive electrode conductor and a second positive electrode binder.

[0046] The present application also proposes a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet of the lithium-ion battery described in the present application or the positive electrode sheet of the lithium-ion battery obtained by the preparation method described in the present application. The negative electrode sheet, the electrolyte, and the separator are all well known to those skilled in the art, and the preparation of the battery is also well known to those skilled in the art, and will not be described in detail in the present application.

[0047] The present application also proposes an electric vehicle, comprising the lithium-ion battery of the present application.

[0048] The technical solution of the present application is further described below with reference to a number of embodiments.

[0049] Example 1

[0050] 1) Preparation of positive electrode for lithium-ion batteries

[0051] Preparation of the first active material layer: Weigh 65g of N-methylpyrrolidone, then weigh 3g of polyvinylidene fluoride, 1g of carbon nanotubes, and 100g of LiFePO4 powder in turn and disperse them into N-methylpyrrolidone. The total dispersion time is 2h to form a first positive electrode slurry; wherein, the average particle size D501 of the LiFePO4 powder is 1.26μm, and the particle size distribution of the LiFePO4 powder is (D901-D101) / D501 is 2.1. The first positive electrode slurry is evenly coated on the surface of the current collector aluminum foil, placed in an oven and dried at 110°C to form a first active material layer on the surface of the aluminum foil.

[0052] Preparation of the third active material layer: Weigh 48g of N-methylpyrrolidone, then weigh 2g of polyvinylidene fluoride, 1.5g of carbon nanotubes, and 100g of LiNi0.8Co0.1Mn0.1O2 powder in turn and disperse them in N-methylpyrrolidone. The total dispersion time is 2h to form a second positive electrode slurry, wherein the average particle size D502 of LiNi0.8Co0.1Mn0.1O2 powder is 3.8μm, and the particle size distribution of LiNi0.8Co0.1Mn0.1O2 powder is (D902-D102) / D502 is 2.1. The second positive electrode slurry is evenly coated on the surface of the formed first active material layer, placed in an oven and dried at 110°C to form a third active material layer on the surface of the first active material layer.

[0053] Preparation of the second active material layer: weigh 65g of N-methylpyrrolidone, then weigh 3g of vinylidene fluoride, 1g of carbon nanotubes, and 100g of LiFePO4 powder in turn and disperse them in N-methylpyrrolidone for a total dispersion time of 2h to form a third positive electrode slurry; wherein, the average particle size D501 of the LiFePO4 powder is 1.26μm, and the particle size distribution of the LiFePO4 powder is (D901-D101) / D501 is 2.1. The third positive electrode slurry is evenly coated on the surface of the third active material layer, placed in an oven and dried at 110°C to form a second active material layer on the surface of the third active material layer; thereby, a lithium-ion battery positive electrode sheet is prepared, which is then pressed and rolled to form a positive electrode sheet.

[0054] The surface density of each layer is controlled so that after roller pressing, the thickness of the first active material layer is 6 μm, the thickness of the ternary layer is 29 μm, and the thickness of the second active material layer is 23 μm;

[0055] The above three-layer electrode can also be coated and baked at one time by multi-layer coating equipment.

[0056] 2) Preparation of negative electrode sheets for lithium-ion batteries

[0057] Graphite is used as the negative electrode active material, a mixture of styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) is used as a binder, and water (H2O) is used as a solvent. The mixture is evenly mixed in a mass ratio of graphite: SBR: CMC: H2O = 100: 3: 2: 50 to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil, placed in an oven at 90° C. to dry for 24 hours, and then pressed and rolled to make a negative electrode sheet.

[0058] 3) Preparation of batteries:

[0059] Celgard 2400 polypropylene porous membrane was used as the diaphragm, and a mixed solution of 1 mol / L LiPF6 in ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1:1) was used as the electrolyte; in a glove box filled with argon, the above-mentioned positive electrode sheet and negative electrode sheet were assembled to obtain battery S1.

[0060] Embodiment 2-embodiment 8 are different from embodiment 1 only in that the thickness of the first active material layer, the third active material layer and the second active material layer of the prepared positive electrode sheet are different, and the average particle size and particle size distribution of LiFePO4 or LiNi0.8Co0.1Mn0.1O2 in each layer are different. Batteries S2-S6 are prepared respectively, as shown in Table 1;

[0061] Comparative Example 1

[0062] Weigh 50 g of N-methylpyrrolidone, then weigh 2.43 g of polyvinylidene fluoride, 56.8 g of LiNi0.8Co0.1Mn0.1O2 powder, 43.2 g of LiFePO4 powder, and 1.28 g of carbon nanotubes in turn and disperse them in N-methylpyrrolidone for a total dispersion time of 2 h to form a positive electrode slurry, wherein the average particle size D502 of the LiNi0.8Co0.1Mn0.1O2 powder is 3.8 μm, and the particle size distribution (D902-D102) / D502 of the LiNi0.8Co0.1Mn0.1O2 powder is 2.1, the average particle size D501 of the LiFePO4 powder is 1.26 μm, and the particle size distribution (D901-D101) / D501 of the LiFePO4 powder is 2.1; The positive electrode slurry is uniformly coated on the surface of the current collector aluminum foil, placed in an oven and dried at a temperature of 110°C, forming a positive electrode material layer mixed with lithium iron phosphate and nickel-cobalt-manganese ternary materials on the surface of the aluminum foil, and then pressed and rolled to form a positive electrode sheet, wherein the thickness of the positive electrode material layer is 58μm; graphite is used as the negative electrode active material, a mixture of styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) is used as a binder, and water (H2O) is used as a solvent. The graphite: SBR: CMC: H2O is mixed uniformly in a mass ratio of 100:3:2:50 to obtain a negative electrode slurry; the negative electrode slurry is coated on a copper foil, placed in an oven at 90°C to dry, and then pressed and rolled to form a negative electrode sheet; Celgard2400 polypropylene porous membrane is used as a diaphragm, 1mol / L A mixed solution of LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1:1) is used as the electrolyte; in a glove box filled with argon, the above-mentioned positive electrode sheet and negative electrode sheet are assembled to obtain a battery DS1.

[0063] Comparative Example 2

[0064] Weigh 45g of N-methylpyrrolidone, then weigh 2g of polyvinylidene fluoride, 1.5g of carbon nanotubes, and 100g of LiNi0.8Co0.1Mn0.1O2 powder in turn and disperse them in N-methylpyrrolidone for a total dispersion time of 2h to form a positive electrode slurry, wherein the average particle size D502 of the LiNi0.8Co0.1Mn0.1O2 powder is 3.8μm, and the particle size distribution (D902-D102) / D502 of the LiNi0.8Co0.1Mn0.1O2 powder is 2.1. The positive electrode slurry is uniformly coated on the surface of the current collector aluminum foil, placed in an oven and dried at 110°C to form a positive electrode material layer containing nickel-cobalt-manganese ternary material on the surface of the aluminum foil, and then pressed and rolled to form a positive electrode sheet, wherein the positive electrode material The thickness of the material layer is 46 μm; graphite is used as the negative electrode active material, a mixture of styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) is used as a binder, and water (H2O) is used as a solvent. The mixture is evenly mixed in a mass ratio of graphite: SBR: CMC: H2O = 100: 3: 2: 50 to obtain a negative electrode slurry; the negative electrode slurry is coated on a copper foil, placed in an oven at 90° C. to dry for 24 hours, and then pressed and rolled to form a negative electrode sheet; a celgard 2400 polypropylene porous membrane is used as a diaphragm, and a mixed solution of 1 mol / L LiPF6 of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1: 1) is used as an electrolyte; in a glove box filled with argon, the above-mentioned positive electrode sheet and negative electrode sheet are assembled to obtain a battery DS2.

[0065] Comparative Example 3

[0066] Weigh 60g of N-methylpyrrolidone, then weigh 3g of polyvinylidene fluoride, 1g of carbon nanotubes, and 100g of LiFePO4 powder in turn and disperse them in N-methylpyrrolidone for a total dispersion time of 2h to form a positive electrode slurry; wherein the average particle size D501 of the LiFePO4 powder is 1.26μm, and the particle size distribution (D901-D101) / D501 of the LiFePO4 powder is 2.1. The positive electrode slurry is uniformly coated on the surface of the current collector aluminum foil, placed in an oven and dried at a temperature of 110°C to form a positive electrode material layer containing lithium iron phosphate on the surface of the aluminum foil, and then After pressing and rolling, a positive electrode sheet is prepared, wherein the thickness of the positive electrode material layer is 83 μm; graphite is used as the negative electrode active material, a mixture of styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) is used as a binder, and water (H2O) is used as a solvent, and the mixture is uniformly mixed in a mass ratio of graphite: SBR: CMC: H2O = 100: 3: 2: 50 to obtain a negative electrode slurry; the negative electrode slurry is coated on a copper foil, placed in an oven at 90° C. and dried for 24 hours, and then pressed and rolled to prepare a negative electrode sheet; a celgard 2400 polypropylene porous membrane is used as a separator, and a mixed solution of 1 mol / L LiPF6 of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1: 1) is used as an electrolyte; in a glove box filled with argon, the above-mentioned positive electrode sheet and negative electrode sheet are assembled to obtain a battery DS3.

[0067] Table 1

[0068]

[0069] Among them, the average particle size and particle size distribution of LiFePO4 and LiNi0.8Co0.1Mn0.1O2 in Examples 1-8 and Comparative Examples 1-3 are measured by a laser particle size analyzer, specifically: 5 g of sample is ultrasonically dispersed in 1000 ml of deionized water for 5 minutes, and then transported to a laser particle size analyzer (instrument model: Malvern 2000 / 3000 laser particle size analyzer) through a sampling system for testing, and the particle volume distribution D50 (volume distribution D50 means: the sum of the volume of particles with a particle size less than or equal to D50 accounts for 50% of the total volume of the sample) is used as the average particle size of the material.

[0070] The battery S1-S8 of Examples 1-8 and the battery DS1-DS3 of Comparative Examples 1-3 were tested for gram capacity, DC internal resistance, discharge capacity, cycle retention rate, and longitudinal thermal diffusion rate of the pole piece. The specific test results are shown in Table 2. The test method for the gram capacity of the positive electrode mixture is: the battery is charged and discharged between the voltage range of 2.0-4.25V, wherein the battery is charged to 4.25V at a constant current of 0.33C during charging, and then charged at a constant voltage with a cutoff current of 0.05C, and discharged to 2.0V at a constant current of 0.33C during discharge. The charge and discharge cycle is performed 3 times in this way, and the discharge capacity after the third cycle is taken and divided by the mass of the positive electrode material layer on the pole piece to obtain the positive electrode gram capacity of the battery.

[0071] The test method of DC internal resistance is: charge the battery to 50% SOC, then let it stand for 1 hour, record the battery voltage V1 at this time, then discharge it at a current of 1.5C0 for 30 seconds (C0 is the capacity of the battery at 0.33C charge and discharge), and record the battery voltage V2 at the end of discharge. The DC internal resistance DCIR is calculated by the following formula: DCIR = (V1-V2) / 1.5C0.

[0072] The test method for cycle performance is: charge the battery to 4.25V at a constant current of 0.5C0, let it stand for 0.5h, then discharge it to 2.0V at a constant current of 0.5C0, let it stand for 0.5h, and cycle it 1000 times according to this step.

[0073] The test method for the longitudinal thermal diffusion rate of the electrode is as follows: charge the battery to a fully charged state (4.25V), take out the positive electrode, stack 30 layers of positive electrode sheets, place temperature sensors between the electrode sheets, and then use a fully charged ternary electrode core to puncture the top layer, and test the time required for the surface temperature of the bottom positive electrode sheet to reach 200°C.

[0074] Table 2

[0075]

[0076] It can be seen from Table 2 that the battery prepared by using the positive electrode sheet of the lithium ion battery of the present application has a higher rate discharge retention rate and a better retention rate of 45°C cycle than the battery using lithium iron phosphate alone as the positive electrode material, or the battery using nickel-cobalt-manganese ternary material alone as the positive electrode material, or the battery using lithium iron phosphate and ternary material mixed as the positive electrode material in the prior art. At the same time, the thermal diffusion time of the electrode piece is greatly increased, indicating that the multi-layer coated electrode piece has better safety performance; and the battery prepared by the positive electrode sheet of the lithium ion battery of the present application has a lower impedance and a higher discharge rate than the existing battery using lithium iron phosphate alone as the positive electrode material, or the battery using lithium iron phosphate and ternary material mixed as the positive electrode material.

[0077] As can be seen from Table 1, the positive electrode sheet of the lithium-ion battery provided in the present application has a lithium iron phosphate layer on the side close to the current collector and a lithium iron phosphate layer on the side close to the separator, and a third active material layer is included in the middle. The thickness of each layer is controlled or the thickness of each layer is controlled with the particle size of the lithium iron phosphate powder and the particle size of the nickel-cobalt-manganese ternary material powder so as to satisfy (L1 / D501) / (L2 / D502)≤8, 0.05≤(L3 / D503) / (L2 / D502)≤8. The prepared positive electrode sheet is applied to batteries, which have better safety performance, higher discharge rate and better cycle performance. This is because the electrode sheet that meets this condition has a low overall tortuosity and faster lithium ion diffusion. At the same time, by controlling the relationship between the thickness ratio of lithium iron phosphate and the ternary material and the particle size, the lithium iron phosphate can have a better protective effect on the electrode and the electrode can have a higher energy density.

[0078] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A positive electrode sheet for a lithium ion battery, characterized in that: The invention comprises a positive electrode current collector, a first active material layer located on the surface of the positive electrode current collector, a second active material layer close to one side of the separator of the lithium ion battery, and a third active material layer located between the first active material layer and the second active material layer, wherein the active materials in the first active material layer and the second active material layer are the same or different, and the active materials in the first active material layer and the second active material layer respectively comprise LiMPO4, wherein M is selected from one or more of Mn, Fe, Co, Ni, and Ti; the active material in the third active material layer comprises Li x Ni a Co b Mn c A 1-a-b-c O2, wherein 0.9≤x≤1.1, 0.3≤a≤0.95, 0≤b≤0.5, 0≤c≤0.5, A is selected from one or more of Zr, Ti, Y, Al, Ba, Sr; The positive electrode sheet comprises a positive electrode current collector, a first active material layer located on the surface of the positive electrode current collector, a third active material layer located on the surface of the first active material layer on the side facing away from the positive electrode current collector, and a second active material layer located on the surface of the third active material layer on the side facing away from the first active material layer; The thickness of the first active material layer is L1, the thickness of the second active material layer is L2, and the thickness of the third active material layer is L3, L1+L2+L3=L; the relationship between the thickness L1 of the first active material layer, the thickness L2 of the second active material layer and the thickness L3 of the third active material layer satisfies: 1μm≤L1≤0.9*L, 1μm≤L2≤0.9*L, 0.1*L≤L3≤0.8*L.

2. The positive electrode sheet of a lithium-ion battery according to claim 1, characterized in that: The relationship among the thickness L1 of the first active material layer, the thickness L2 of the second active material layer and the thickness L3 of the third active material layer satisfies: 0.3*L≤L1≤0.8*L, 0.2L≤L2≤0.6*L, 0.1*L≤L3≤0.6*L.

3. The positive electrode sheet of a lithium ion battery according to claim 1, characterized in that: In the first active material layer, the median particle size of the active material LiMPO4 is D501, in the second active material layer, the median particle size of the active material LiMPO4 is D502, and in the third active material layer, the median particle size of the active material Li x Ni a Co b Mn c A 1-a-b-c The median particle size of O2 is D503, where (L1 / D501) / (L3 / D503)≤8, 0.05≤(L2 / D502) / (L3 / D503)≤8.

4. The positive electrode sheet of a lithium ion battery according to claim 3, characterized in that: The median particle size D501 of the active material LiMPO4 in the first active material layer, the median particle size D502 of the active material LiMPO4 in the second active material layer, and the median particle size D503 of the active material Li in the third active material layer x Ni a Co b Mn c A 1-a-b-c The relationship between the median particle size D503 of O2 satisfies: 0.1≤(L1 / D501) / (L3 / D503)≤6, 0.2≤(L2 / D502) / (L3 / D503)≤6.

5. The positive electrode sheet of a lithium ion battery according to claim 1, characterized in that: In the third active material layer, the active material Li x Ni a Co b Mn c A 1-a-b-c The molar content of Ni in O2 is ε, the thickness of the first active material layer L1, the thickness of the second active material layer L2 and the thickness of the active material Li in the third active material layer x Ni a Co b Mn c A 1-a-b-c The relationship between the molar content ε of the Ni element in O2 satisfies: 0.1≤L1 / (ε*L3)≤5.

6. The positive electrode sheet of a lithium ion battery according to claim 3, characterized in that: The median particle sizes D501 and D502 of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 0.3μm≤D501≤1.5μm, 0.3μm≤D502≤1.5μm; the particle size distribution of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 1≤(D901-D101) / D501≤4, 1≤(D902-D102) / D502≤4.

7. The positive electrode sheet of a lithium-ion battery according to claim 6, characterized in that: The median particle sizes D501 and D502 of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 0.6μm≤D501≤1.2μm, 0.6μm≤D502≤1.2μm; the particle size distribution of the active material LiMPO4 in the first active material layer and the second active material layer respectively satisfy: 2≤(D901-D101) / D501≤3, 2≤(D902-D102) / D502≤3.

8. The positive electrode sheet of a lithium ion battery according to claim 2, characterized in that: The active material Li in the third active material layer x Ni a Co b Mn c A 1-a-b-c The median particle size D503 of O2 satisfies: 1 μm≤D503≤15 μm; the active material Li in the third active material layer x Ni a Co b Mn c A 1-a-b-c The particle size distribution of O2 satisfies: 2≤(D903-D103) / D503≤3.

9. The positive electrode sheet of a lithium-ion battery according to claim 8, characterized in that: The active material Li in the third active material layer x Ni a Co b Mn c A 1-a-b-c The median particle size D503 of O2 satisfies: 3μm≤D503≤6μm.

10. The positive electrode sheet of a lithium ion battery according to claim 1, characterized in that: The positive electrode conductive agents in the first active material layer, the second active material layer and the third active material layer are each independently selected from one or more of carbon nanotubes, conductive carbon black, and graphene; the positive electrode binders in the first active material layer, the second active material layer and the third active material layer are each independently selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile and polyacrylate.

11. The positive electrode sheet of a lithium ion battery according to claim 1, characterized in that: The active material LiMPO4 includes LiFePO4, the active material Li x Ni a Co b Mn c A 1-a-b-c O2 includes LiNi 0.8 Co 0.1 Mn 0.1 O2.

12. A method for preparing a positive electrode sheet of a lithium ion battery, the method comprising: A positive electrode current collector is provided, a first active material layer is prepared on at least one side of the positive electrode current collector, at least one third active material layer is prepared on the surface of the first active material layer, and a second active material layer is prepared on the surface of at least one third active material layer, wherein the second active material layer is located on a side of a separator close to a lithium ion battery; the active material in the first active material layer and the active material in the second active material layer are the same or different, and the active material in the first active material layer and the active material in the second active material layer include LiMPO4, wherein M is selected from one or more of Mn, Fe, Co, Ni, and Ti; the active material in the third active material layer includes Li x Ni a Co b Mn c A 1-a-b-c O2, wherein 0.9≤x≤1.1, 0.3≤a≤0.95, 0≤b≤0.5, 0≤c≤0.5, A is selected from one or more of Zr, Ti, Y, Al, Ba, Sr; The positive electrode sheet comprises a positive electrode current collector, a first active material layer located on the surface of the positive electrode current collector, a third active material layer located on the surface of the first active material layer on the side facing away from the positive electrode current collector, and a second active material layer located on the surface of the third active material layer on the side facing away from the first active material layer; The thickness of the first active material layer is L1, the thickness of the second active material layer is L2, and the thickness of the third active material layer is L3, L1+L2+L3=L; the relationship between the thickness L1 of the first active material layer, the thickness L2 of the second active material layer and the thickness L3 of the third active material layer satisfies: 1μm≤L1≤0.9*L, 1μm≤L2≤0.9*L, 0.1*L≤L3≤0.8*L.

13. The method for preparing a positive electrode sheet of a lithium ion battery according to claim 12, characterized in that: The method for preparing a first active material layer on the surface of the positive electrode current collector comprises: coating a first positive electrode slurry on at least one side of the surface of the positive electrode current collector and drying the first positive electrode slurry, wherein the first positive electrode slurry comprises an active material LiMPO4, a first positive electrode conductor, a first positive electrode binder, and a first solvent; the method for preparing a third active material layer on the surface of the first active material layer comprises: coating a third positive electrode slurry on a side of the surface of the first active material layer away from the current collector and drying the third positive electrode slurry comprises an active material Li x Ni a Co b Mn c A 1-a-b-c O2, a third positive electrode conductor, a third positive electrode binder and a third solvent; a method for preparing a second active material layer on the surface of the third active material layer comprises: coating a second positive electrode slurry on the surface of the third active material layer and drying it, wherein the second positive electrode slurry comprises an active material LiMPO4, a second positive electrode conductor, a second positive electrode binder and a second solvent.

14. The method for preparing a positive electrode sheet of a lithium ion battery according to claim 12, characterized in that: The method comprises: coating a first positive electrode slurry on the surface of a positive electrode current collector to form a first coating layer, wherein the first positive electrode slurry comprises an active material LiMPO4, a first positive electrode conductive agent and a first positive electrode binder; a method for preparing a third active material layer on the surface of the first active material layer comprises: coating a third positive electrode slurry on a side of the first coating layer away from the current collector to form a second coating layer, wherein the third positive electrode slurry comprises an active material Li x Ni a Co b Mn c A 1-a-b-c O2, a third positive electrode conductor and a third positive electrode binder; coating the second positive electrode slurry on the surface of the second coating layer away from the first coating layer to form a third coating layer and drying it, the second positive electrode slurry comprising active material LiMPO4, a second positive electrode conductor and a second positive electrode binder.

15. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises the positive electrode sheet of the lithium ion battery according to any one of claims 1 to 13 or the positive electrode sheet of the lithium ion battery obtained by the preparation method according to any one of claims 12 to 14.

16. An electric vehicle comprising the lithium-ion battery according to claim 15.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery positive electrode material and lithium ion battery

    CN108735968A

  • High-safety positive plate and lithium ion battery thereof

    CN112467107A